2001
DOI: 10.1046/j.1440-1827.2001.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrioid adenocarcinoma arising from adenomyosis: Report and immunohistochemical analysis of an unusual case

Abstract: A case of endometrioid adenocarcinoma arising from adenomyosis is reported. The patient was a 53-year-old woman who complained of vulvar itching. Smear cytology of the endometrium revealed adenocarcinoma. Magnetic resonance imaging of the pelvis revealed a lesion with a slightly high intensity in the uterine fundus on a T2-weighted image. Semiradical total hysterectomy and bilateral adnexectomy were performed, followed by chemotherapy. Histologically, the lesion in the uterine fundus was composed mostly of ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…They reviewed 4 cases of their own patients and 26 previously reported cases of patients in 2002 with malignant neoplasm arising from adenomyosis (2). We found 9 additional cases of patients with malignant neoplasms arising from adenomyosis in English literature (3)(4)(5)(6)(7)(8)(9)(10)(11). Most of the malignant tumors arising The diagnostic criteria for ovarian carcinoma arising from endometriosis were originally proposed by Sampson (12) and modified by Colman and Rosenthal (13) so as to apply the criteria to carcinomas developing from adenomyosis as follows: a) the carcinoma should be absent in the normally situated endometrium and elsewhere in the pelvis; b) the carcinoma should be actually observed to be arising from the epithelium of the areas of adenomyosis and not invading it from some other source; and c) endometrial stromal cells should be surrounding the aberrant glands to support the diagnosis of adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…They reviewed 4 cases of their own patients and 26 previously reported cases of patients in 2002 with malignant neoplasm arising from adenomyosis (2). We found 9 additional cases of patients with malignant neoplasms arising from adenomyosis in English literature (3)(4)(5)(6)(7)(8)(9)(10)(11). Most of the malignant tumors arising The diagnostic criteria for ovarian carcinoma arising from endometriosis were originally proposed by Sampson (12) and modified by Colman and Rosenthal (13) so as to apply the criteria to carcinomas developing from adenomyosis as follows: a) the carcinoma should be absent in the normally situated endometrium and elsewhere in the pelvis; b) the carcinoma should be actually observed to be arising from the epithelium of the areas of adenomyosis and not invading it from some other source; and c) endometrial stromal cells should be surrounding the aberrant glands to support the diagnosis of adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…A case with positive preoperative endometrial cytology containing many atypical papillary clusters with features of adenocarcinoma was reported by Sasaki et al [45] who maintained that the origin of the cells was uncertain. Also, Kawana et al [75] described a case where three-dimensional clusters of malignant cells were found in endometrial cytology.…”
Section: Endometrial Cancer Arising Within Adenomyotic Focimentioning
confidence: 99%
“…Thus, the condition is also known as ''internal'' endometriosis. 16 Whether internal adenomyosis is also associated with an increased risk of certain malignancies remains unclear. Currently, there are a paucity of data on the association between adenomyosis and cancer risk.…”
mentioning
confidence: 99%
“…Currently, there are a paucity of data on the association between adenomyosis and cancer risk. 16,17 Therefore, we examined the risk of cancer, particularly ovarian, endometrial, mammary, and CRC, in women with endometriosis or adenomyosis using a well-established nationwide population-based administrative database.…”
mentioning
confidence: 99%